2012
DOI: 10.1063/1.3671450
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of vibrational frequencies of possible intermediates and side products of the methanol synthesis on ZnO($000\overline{1}$0001¯) by ab initio calculations

Abstract: We used ab initio density functional theory in combination with an embedded cluster approach to calculate vibrational spectra and formation enthalpies of possible intermediates and side products (spectator species) in the synthesis of methanol out of syngas on the ZnO(0001) surface. Our investigations are based upon our previous work on possible reaction pathways and activation barriers for this reaction at oxygen vacancies on ZnO(0001). We present and discuss calculated vibrational frequencies of short-living… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
25
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 47 publications
1
25
1
Order By: Relevance
“…As assignment of spectra is achieved by comparing measured [2] and computed frequencies, it is clear that the ability to compute accurately vibrational frequencies is important for guiding material design. Today, with rare exceptions [3][4][5][6][7], such assignment is based on uncoupled harmonic frequencies provided by widely used DFT codes [8,9]. Anharmonicity and coupling effects can shift frequencies by dozens cm -1 and hinder assignment [3,10], yet their inclusion in calculations has been too computationally expensive for most labs.…”
Section: Introductionmentioning
confidence: 99%
“…As assignment of spectra is achieved by comparing measured [2] and computed frequencies, it is clear that the ability to compute accurately vibrational frequencies is important for guiding material design. Today, with rare exceptions [3][4][5][6][7], such assignment is based on uncoupled harmonic frequencies provided by widely used DFT codes [8,9]. Anharmonicity and coupling effects can shift frequencies by dozens cm -1 and hinder assignment [3,10], yet their inclusion in calculations has been too computationally expensive for most labs.…”
Section: Introductionmentioning
confidence: 99%
“…While ZnO itself contributed to the adsorption of CO 2 and formation of carbonate, Cu as a dopant had increased the adsorption capacity of the carbonate and even catalyzed transformation of carbonates into formate[177], which is an important intermediate in methanol synthesis.Comprehensive experimental and theoretical work has been done in the past on CO 2 adsorption, particularly on the (000 ), (0001), and (10 0) facets. However, no agreement on the adsorption geometries exists, because some studies showed carbonate or bent CO 2 formation, while others argued that the adsorption is mostly physical[176,[179][180][181][182][183][184]. The structure-activity relationship (SAR) of CO 2 adsorption on ZnO surface was studied.…”
mentioning
confidence: 99%
“…The authors' view is somehow shared byDutta et al, where, in their DFT study, During adsorption, the CO 2 molecule anchors itself to the surface by orienting one of its oxygen atoms into a vacant site and accepting the localized, trapped electron there. Further bending towards one of the neighboring ions would result in the formation of a carboxylate ion, rather than carbonate[185].Koßmann et al applied ab initio DFT study with an embedded cluster approach to calculate vibrational spectra for various molecules, as intermediates for CO 2 to methanol conversion over a ZnO(0001 ) surface[183]. Polydentate and monodentate carbonate were expected, along with formate species, as the calculations were carried out using a Turbomole program package with…”
mentioning
confidence: 99%
“…Concerning the pathways involved, a wide variety of proposed reaction intermediate species have been identified via experiment 20, 46–56 and theory 19, 57–61, which certainly is an incomplete list. Although the basic steps in the reduction process via a stepwise hydrogenation of CO are mechanistically rather simple on paper the sheer number of the obtained (and partially conflicting) results suggests that effectively several reaction channels might be accessible for methanol synthesis when taking place over the heterogeneous catalyst.…”
Section: Introductionmentioning
confidence: 99%